2021
DOI: 10.11609/jott.6945.13.9.19212-19222
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the species richness and composition of bird species in a community managed forest of Nepal

Abstract: There exists limited information on biodiversity including avifaunal diversity and habitat condition in community forests (CF) of Nepal; thus we aimed to fulfill such gaps in Tibrekot CF of Kaski district. We used the point count method for assessing bird diversity and laid out a circular plot size of radius 5-m within 15-m distance from each point count station for recording the biophysical habitat characteristics. Bird species’ diversity, richness and evenness were calculated using popular indexes and Genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
(36 reference statements)
4
3
0
Order By: Relevance
“…We found the insectivore guild to be the most common feeding guild along the Himalayan forest, corresponding with previous studies [ 23 , 33 ]. This guild is supported by the abundant arthropods, which are also reported to be higher in the mid-hills region [ 56 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We found the insectivore guild to be the most common feeding guild along the Himalayan forest, corresponding with previous studies [ 23 , 33 ]. This guild is supported by the abundant arthropods, which are also reported to be higher in the mid-hills region [ 56 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our study found higher species richness in the winter season for both forests. The higher number of bird species in the winter (153 species) is due to the addition of the winter visitors (13 species) and a partial migrant (1 species) to the resident birds (139 species), which coincides with the results of Poudel et al [ 33 ], a study conducted in the same TCF. The winter migrants in our study area mainly come from northern countries such as China, Mongolia, Korea, Siberia, and Central Asia in search of warmer places, whereas summer visitors come to Nepal from southern countries such as India, Sri Lanka, and Sub-Saharan Africa in search of food and breeding sites [ 38 , 39 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similarly, the higher Margalef value indicates the suitability of habitat for community stability with the longer food chain and complex food web (Margalef, 1956). The Margalef value of the study area is similar to the observation of Poudel et al (2021). Similarly, the higher Pielou's Evenness Index indicates that the population size of each of the species present in the area is near complete evenness, which is similar to the observation of Poudel et al (2021).…”
Section: Species Diversitysupporting
confidence: 77%
“…Comparison between the diversity of birds in different seasons was calculated using the Shannon-Weiner Diversity Index (1949) for different seasons (Katuwal et al 2016;, Katuwal et al, 2018;Pragasanand Madesh 2018;Joshi et al, (2021). Inskipp et al (2016) and CITES (2017) were followed to assess the nomenclature and classification as well as conservation status of species.…”
Section: Discussionmentioning
confidence: 99%